COMMUNITY IDENTITY AS AN INTEGRATED PART OF PLACE-IDENTITY (Symposium on Natural and Applied Sciences, 2026)
This article explores community identity as an integral component of place-identity in Louise Erdrich’s novel The Plague of Doves. The study focuses on the ways in which belonging to a family, community, region, and cultural memory shapes the self-perception of the characters. Drawing on Lee Cuba and David M. Hummon’s theoretical views on identification with dwelling, community, and region, the paper examines how local attachment, intergenerational memory, storytelling, and indigenous cultural heritage contribute to the construction of identity. Particular attention is paid to Evelina’s narrative perspective and Mooshum’s oral stories, which function as important sources of cultural continuity and communal belonging. The analysis shows that Erdrich represents place not merely as a geographical setting, but as a living cultural and emotional space where personal and collective identities intersect. The article argues that community identity in the novel is formed through shared history, kinship ties, oral tradition, and emotional attachment to land. Thus, The Plague of Doves demonstrates the inseparable connection between place, memory, and the formation of the self.
Keywords: place-identity, community identity, belonging, Louise Erdrich, The Plague of Doves, indigenous culture, storytelling, regional identity